Analisis Strategi Peningkatan Pendapatan Asli Daerah dalam Pelaksanaan Otonomi Daerah di Kota Bandar Lampung - Tri Lestira Putri Warganegara; Revita Sari; Iskandar A.A (Politeknik Negeri Lampung, 2019)
In estimating the potential of the region, information and benchmarks are needed that are real in the field and are desired by the community concretely. One of the financial benchmarks that can be used to see regional readiness in implementing autonomy is to measure how far the financial capacity of a region is. While the regional financial capacity is usually measured by the amount of contribution of Regional Original Income (PAD). Data collection techniques used were interviews and documentation and data analysis techniques using qualitative descriptive. The results of the study using SWOT analysis showed that the strength of Bandar Lampung City Revenue Service in an effort to increase local revenue is to have qualified human resources (quite competent), the potential of the Bandar Lampung City Revenue Office is quite high quality in carrying out its main tasks and functions, there are job descriptions clear in carrying out their main tasks and functions and supporting adequate operational budget. The weaknesses are the weak function of coordination between and inter agencies, the weak monitoring function, inadequate office facilities and infrastructure and the weak application of sanctions for violators of taxes and levies. Potential objects as well as high taxpayers and retributions and strong political support for the elected Mayor and Deputy Mayor are opportunities for the Bandar Lampung City Revenue Service in an effort to increase local revenues and challenges or threats of Bandar Lampung City Revenue Service in an effort to increase local revenue is the scope of the area of potential that is quite broad and the low public awareness of taxpayers and levies.Keywords: Increased PAD, SWOT Analysis